HUBUNGAN INTENSITAS KEBISINGAN DAN MASA KERJA DENGAN PENINGKATAN TEKANAN DARAH PADA PEKERJA POLYESTER PT INDONESIA TORAY SYNTHETICS KOTA TANGERANG - Anju Stefani; Onny Setiani; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2018)
Noise is an undesirable sound and can cause health problem. Continuously noised can lead to cardiovascular disorders such as increase of blood pressure. The purpose of this study was to determine the association between noise intensity and lenght of work with increased blood pressure on the polyester workers in Indonesia Toray Synthetics Company, Tangerang Regency. This research was an observational analitic with cross sectional design. The sample of this research were 56 workers in polyester area and taken based simple random sampling. Data collecting using questionnaires. Data analysis using Chi Square Test and Paired T Test. The results of noise intensity show there is 6 works location in polyester which exceed 85 dBA. There is a difference in blood pressure before and after work where systolic and diastolic (p=0,000). The results of this research showed that there was releated between noise intensity and increased diastolic blood pressure p=0,039 (RP=1,594, CI 95%= 1,012-2,508), while there was no releated between noise intensity and increased systolic blood pressure p=0,375 (RP=1,282, CI 95%= 0,829-1,982), work period with increased systolic pressure p=0,793 (RP=0,890, CI 95%= 0,59-1,342), and work period with increased diastolic p=1 (RP=1,038, CI 95%= 0,731-1,474). From this study, it can be concluded that increase of diastolic blood pressure influenced by noise intensity. Polyester workers are advised to always use ear protection when doing work and sufficient water during work.